Person-Centered Preventive Health Care: Gathering Stakeholder Input on Evidence and Implementation - Leila C. Kahwati, MD, MPH; Hanan J. Aboumatar, MD, MPH; Alison K. Banger, MPH; Sarah I. Bean, MPH; Laurie W. Hinnant, PhD; Daniel E. Jonas, MD, MPH; Julia M. Kim, MD, MPH; Jennifer S. Lin, MD, MCR; Carrie D. Patnode, PhD; Meagan R. Pilar, PhD; Samantha I. Pitts, MD, MPH; Shivani M. Reddy, MD, MSc; et al. (AJPM Focus, 2025)
Introduction: Clinical preventive services, such as screening tests, vaccinations, behavioral counseling, or preventive medication, are offered to most people on the basis of age, sex, health behaviors, or clinical risk factors, with goals of detecting early disease, preventing future disease, or mitigating the impact of unhealthy behaviors on future health. However, many people do not receive all the recommended services for which they are eligible. Methods: The Agency for Healthcare Research and Quality identified 4 topics for gathering stakeholder input on evidence and implementation for the equitable delivery of clinical preventive services. These included technology, innovative delivery models, public health linkages, and disparities. For each topic, the authors conducted an environmental scan to identify existing programs or interventions to promote the delivery of clinical preventive services, a technical expert panel meeting, and key informant interviews. The authors synthesized input from each topic's technical expert panel and key informant interviews and used inductive reasoning to identify themes. Within each overarching theme, the authors identified subthemes supported by specific statements, examples, and illustrative quotes. Results: A total of 90 individuals participated on stakeholder panels, technical expert panels, or key informant interviews; some individuals participated in multiple roles. Across the topics, the authors identified 3 overarching themes from synthesis of the technical expert panel and key informant interview comments across topics: (1) transitioning to holistic healthcare delivery and financing models, (2) including community and patient voice in healthcare system design, and (3) leveraging technology to improve clinical preventive services delivery. Conclusions: Promoting the equitable delivery of clinical preventive services requires improving access to primary care but also expanding efforts beyond clinical settings to encompass public health and community infrastructure and engagement. Experts recommended that person-centered preventive care should empower patients to make informed decisions about clinical preventive services on the basis of their values, risks, and preferences. This more individualized approach tailored to needs and context may reduce barriers to receipt of clinical preventive services.